Changes in Economic Activities in the Lens of Sociology and Anthropology of Islamic Law - Akbar Muhamad Ashoni; Abdal Abdal (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
Changes in economic activities in Muslim society are phenomena influenced by social, cultural, and legal aspects. Sociology and anthropology of Islamic law play an important role in understanding these dynamics, including how the application of sharia principles adapts to the times. This research uses a qualitative literature study approach, examining written sources from classical texts and academic literature related to the sociology of law, legal anthropology, and Islamic economics. Data were collected from journal articles, books, and open documents through various online repositories, and then analyzed descriptively and holistically, The results of the study show that social and economic changes continue to affect the application of Islamic law and sharia economics. Islamic economic principles that are rooted in the values of monotheism, justice, and morals are the main guidelines in adapting to the development of economic activities. The application of this principle also shows the dynamism in social reality and the importance of understanding the socio-cultural context. The dynamics of this change underscore the need for a comprehensive study of the relationship between legal, social, and economic in the context of Islam. Adjustments to the needs of the times will strengthen the sustainability of the sharia economy and be able to maintain a balance between religious norms and the social needs of the community.